التوازن في شبكة المنظومة الحضرية(دراسة حالة ولاية بسكرة) - بوعافية, عبد الرزاق; علقمة, جمــــــال (Courrier du Savoir, 2018)
The Algerian regions suffer  from many imbalances within their urban system, which have negatively affected the social, economic and urban aspects, forcing many of the population to abandon the less fortunate areas of development programs(poor) to the more affluent (rich) Which has had consequences and problems were represented in urban concentration and urban hegemony, due to the imbalances of the distribution of development projects and spatial dimensions of the regions, and the lack of development policies to develop comprehensive development strategies, which requires the continuation of the search for the best ways to reduce hegemony And the restoration of balance within the regions through the enactment of legislation on the formation of regions, which will be discussed in this paper the province of Biskra state.